PWE-061 Young-onset colorectal cancer presentation in a DGH population compared to older-onset patients. (June 2019) - Xing, Siyao; Pomfret, Suzanne; Landy, Jonathan; Cheetham, Drostan; Catnach, Susan
Abstract : Background and Aims: The incidence of colorectal cancer (CRC) in patients under 50 years of age is increasing although it is still a rare diagnosis in this age group. However, data suggest young-onset CRC patients have a delayed presentation with higher rates of advanced disease stage at diagnosis. Diagnostic algorithms that increase the specificity of investigations for symptomatic patients in this age group are needed. We aimed to assess features of presentation in young-onset CRC patients in our population and to compare features at presentation with older onset patients. Methods: The trust cancer database was reviewed for all patients with a diagnosis of CRC between May 2015 and 2018. Patients diagnosed under the age of 50 were included in the young-onset group. Older onset CRC patients were matched 4:1 by gender and site of tumour (right colon/left colon/rectum). Electronic records were evaluated for presentation and laboratory parameters at diagnosis. Fisher's exact test was used for statistical analysis; odds ratios and confidence intervals were calculated where statistically significant (α 0.05) differences between groups were identified. Data was analysed using GraphPad Prism 5. Results: 43 patients with a diagnosis of CRC aged less than 50 were identified (6% of all CRC diagnoses). 56% were male with a median age of 40 (IQR 3–6). The most common symptoms at presentation were constipation or diarrhoea (44%), pain (42%) and rectal bleeding (37%). 26% had ≥2 symptoms at presentation. None had a documented significant family history of CRC. In young-onset CRC patients, 49% of tumours were in the left colon, 28% in the right colon and 23% in the rectum. 37% were emergency presentations compared with 26% in the older onset CRC group (ns). 56% presented with Stage 3 or 4 disease compared with 49% in patients ≥50 years (ns). 1-year survival was 93% in young-onset CRC patients v 86% in patients ≥50 years (ns). 51% of young-onset CRC v 31% in patients ≥50 years were anaemic at presentation (p=0.02; OR 2.3 95% CI 1.–.5). 26% of young-onset CRC v 10% in patients ≥50 years had elevated platelet counts at diagnosis (p=0.02; OR 2.9 95% CI 1.3- 6.8). Conclusion: In our population young-onset CRC patients there was a trend towards higher rates of emergency presentation and advanced disease stage, as well as a higher 1-year survival rates, although these were not statistically significant compared to older onset CRC patients. A significantly higher proportion of young-onset CRC patients were found to be anaemic and or have elevated platelet counts at diagnosis. Elevated platelet count as well as blood haemoglobin should be investigated further leading to possible incorporation into diagnostic algorithms that might increase the specificity of investigation for symptomatic patients in this age group.